Non-intubated Thoracoscopic Surgery—Pros and Cons - Janík, Miroslav; Juhos, Peter; Lučenič, Martin; Tarabová, Katarína (Frontiers in Surgery, 2021)
Pulmonary resection by video-assisted thoracoscopic surgery with single-lung ventilation has become a standardized modality over the last decades. With the aim to reduce surgical stress during operation procedures, some have adopted a uniportal approach in pulmonary resection as an alternative to multiportal VATS. The ERAS program has been widely spread to achieve even better outcomes. In 2004, Pompeo reported the resection of pulmonary modules by conventional VATS under intravenous anesthesia without endotracheal intubation. Within less than a decade thereafter, complete VATS pulmonary resections under anesthesia without endotracheal intubation had been reported for a range of thoracoscopic procedures. Avoiding tracheal intubation under general anesthesia can reduce the incidence of complications such as intubation-related airway trauma, residual neuromuscular blockade, ventilation-induced lung injury, impaired cardiac performance, and postoperative nausea. Numerous studies can be found especially from Asian countries, focusing on comparison of intubated and non-intubated procedures showing that non-intubated VATS could reduce the rate of postoperative complications, shorten hospital stay and decrease the perioperative mortality rate, indicating that non-intubated VATS is a safe, effective and feasible technique for thoracic disease. However, if we look closely at all studies, it is obvious that there are no significant differences between intubated and non-intubated surgery in terms of the standard procedures and maneuvers. In non-intubated procedures it can be less comfortable for the surgeon to manipulate in the thoracic cavity, but the procedural steps remain the same. All the differences between the intubated and non-intubated operation procedure are found in perioperative management of the patient. The patient is still in deep anesthesia during the procedure and hypecapnia can occur. It is easier to manage this if the patient is intubated. In addition, if a complication occurs during the operation and intubation is required, this can cause an emergent situation, which means that not all patients are suitable for such a procedure, especially those with severe emphysema, obese patients and those with a problematic oropharyngeal configuration-Mallampati score. Moreover, studies on non-intubated thoracic surgery point to shortened hospitalization, faster recovery etc. But there are also studies on intubated uniportal VATS procedures in combination with ERAS protocol showing shortened hospitalization and better outcome for patients. Currently, especially with the use of optical intubation canylas, totally intravenous anesthesia (TIVA), BIS and relaxometer, anesthesia is safe for avoiding airway injury, hypercapnia, and there is minimal risk of residual curarization as well as one of the postoperative lung complications such as microaspiration and atelectasis. In addition, the patient recovers rapidly from anesthesia and can be verticalised and mobilized a couple of hours after the operation. It is desirable to take into consideration what type of patient and what lung disease is suitable for non-intubated technique and what is more convenient for intubation.